THE INFLUENCE OF KAHOOT-BASED LEARNING MEDIA ON STUDENTS LEARNING OUTCOMES IN ISLAMIC EDUCATION SUBJECT FOR SIXTH GRADE AT SD NEGERI 06 MERIGI - Ceshelya Astra; Aniska Septi Sabena; Aida Rahmi Nasution; Mirzon Daheri (Program Studi Pendidikan Agama Islam, 2026)
Learning media play a role as tools that help educators deliver materials so that they are more easily understood by students. Initial observations at SD Negeri 06 Merigi show that some students are not yet able to maintain learning focus, resulting in learning outcomes that have not reached the expected level. Although the teacher has tried several learning models, these efforts did not last long due to low student engagement, and the learning process returned to the lecture method. This study aims to examine the effect of using Kahoot application-based learning media on the learning outcomes of sixth-grade students in Islamic Religious Education at SD Negeri 06 Merigi. The study employed a quantitative approach with a pre-experimental one-group pretest–posttest design. All sixth-grade students were involved as the research sample. The findings show that the average pretest score was 53.33 and increased to 75.00 in the posttest after the implementation of Kahoot. The Paired Samples Test resulted in a significance value of 0.000 (<0.05). These results confirm that the use of the Kahoot application has a significant effect on improving students’ learning outcomes in Islamic Religious Education.